Increase of the Egyptian Government's budget for the Takaful and Karama national cash transfer program - CGIAR Research Program on Policies, Institutions, and Markets (2020)
The Egyptian Government's budget for the Takaful and Karama program increased by 2.7% (i.e. about USD 32M) to reach USD 1.23 billion for FY 21.